Salmonella in Domestic Animals 2013
DOI: 10.1079/9781845939021.0001
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and species concepts in the genus Salmonella .

Abstract: The taxonomy, nomenclature, phylogenetics and molecular epidemiology of Salmonella spp. are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…However, it has also been reported that SA S d may occasionally cause rhinitis or chronic nasal inflammation [10, 11], orchitis [12], or aborted foetuses [4]. As these properties deviate from the classical characteristics of host-restricted, host-adapted or ubiquitous serovars [13], the term sheep associated serovar [6] appears most appropriate to characterise serovar 61: k: 1, 5, (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been reported that SA S d may occasionally cause rhinitis or chronic nasal inflammation [10, 11], orchitis [12], or aborted foetuses [4]. As these properties deviate from the classical characteristics of host-restricted, host-adapted or ubiquitous serovars [13], the term sheep associated serovar [6] appears most appropriate to characterise serovar 61: k: 1, 5, (7).…”
Section: Introductionmentioning
confidence: 99%
“…More than 2,500 Salmonella serovars have so far been identified, while 99% of human and animal infections are caused solely by one subspecies, Salmonella enterica subsp. enterica ( S. enterica ) ( 3 ). With regard to human disease, S. enterica has traditionally been divided into a small number of human-restricted invasive typhoidal Salmonella and thousands of non-typhoidal Salmonella (NTS) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The subspecies enterica (I) groups the majority (1547, 60%) of serovars that affect human and domestic animals (Dekker & Frank, 2015;Grimont & Weill, 2007;OIE, 2012), and those serovars are classified as typhoidal and nontyphoidal Salmonella (NTS) (Sanderson & Nair, 2013). Contaminated meat and poultry products such as commercial table eggs and raw chicken meat constitute the main sources of S. enterica (Ricke & Calo, 2015).…”
Section: Introductionmentioning
confidence: 99%